Elaboration Likelihood Model in Green Consumption: The Role of Social Media in Shaping the Purchase Intentions of Generation Z in Indonesia - Prasojo, Eko; Endarwati, Endarwati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Growing environmental concerns have intensified interest in sustainable consumption, particularly among Generation Z in emerging economies. While prior studies have examined green purchase intention and social media influence, limited research has integrated the Elaboration Likelihood Model (ELM) with subjective norms within the Indonesian digital context, especially on platforms such as TikTok and Instagram. This study addresses this theoretical gap by examining how green information sharing on social media influences green purchase intention through perceived green value and subjective norms. Using a quantitative explanatory design, data were collected from 300 Generation Z social media users in six major Indonesian cities. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to test the proposed hypotheses, including mediation and multi-group analysis based on employment status. The findings demonstrate that green information sharing significantly enhances green purchase intention both directly and indirectly through perceived green value and subjective norms. Subjective norms emerge as a stronger mediating mechanism, highlighting the importance of social influence in a collectivist cultural setting. Additionally, employment status moderates the relationship between subjective norms and purchase intention. The study contributes theoretically by extending ELM within the green consumption domain in a developing-country context and by integrating social influence mechanisms into digital green marketing communication. Practically, the results offer strategic insights for policymakers and marketers to design persuasive green campaigns that combine cognitive and social appeals.